2020
DOI: 10.1002/anie.202005946
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity of Catechols and Amines in High‐Performance Dry/Wet Adhesives

Abstract: The outstanding adhesive performance of mussel byssal threads has inspired materials scientists over the past few decades. Exploiting the amino‐catechol synergy, polymeric pressure‐sensitive adhesives (PSAs) have now been synthesized by copolymerizing traditional PSA monomers, butyl acrylate and acrylic acid, with mussel‐inspired lysine‐ and aromatic‐rich monomers. The consequences of decoupling amino and catechol moieties from each other were compared (that is, incorporated as separate monomers) against a mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 59 publications
5
78
0
Order By: Relevance
“…Since adhesion to surface involves the catechol, Ruiz-Molina and coworkers proposed also the use of PDA analogous demonstrating that some bis-catecholic polymers can be used to coat mesoporous silica NP in order to slow down the release of preloaded model molecules [ 88 ]. Recently, Messersmith and coworkers demonstrated that, indeed, having both catechols and amines combined in the same functional monomer is advantageous for the final adhesion strength: decoupling the two kinds of functional groups, in fact, prevents cooperative effects with an observable worsening of the adhesive performances [ 89 ]. The same author also showed that mechanical properties of PDA coating can be further enhanced, and the roughness reduced, by treatment with blue-diode laser treatment, inducing graphitization while preserving multifunctionality [ 90 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since adhesion to surface involves the catechol, Ruiz-Molina and coworkers proposed also the use of PDA analogous demonstrating that some bis-catecholic polymers can be used to coat mesoporous silica NP in order to slow down the release of preloaded model molecules [ 88 ]. Recently, Messersmith and coworkers demonstrated that, indeed, having both catechols and amines combined in the same functional monomer is advantageous for the final adhesion strength: decoupling the two kinds of functional groups, in fact, prevents cooperative effects with an observable worsening of the adhesive performances [ 89 ]. The same author also showed that mechanical properties of PDA coating can be further enhanced, and the roughness reduced, by treatment with blue-diode laser treatment, inducing graphitization while preserving multifunctionality [ 90 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another open question remains as to whether natural or synthetic analogs of DA/DOPA can undergo similar polymerization routes. [275] Additional uncertainties arise in several themes: [19] i) the role of the adjacency of catecholic and cationic moieties in cooperative adhesion; ii) the degradability and degradation mechanism of PDA and related materials; iii) the mechanism of copolymerization/codeposition. In order to elucidate these, further investigations should follow to gather compelling evidence or full details based on comprehensive decoupling designs, [18,19] macro-to-atomic level analytic tools, [19] and rationale computational simulation, [276] among other tools and resources.…”
Section: Mechanismmentioning
confidence: 99%
“…In the meantime, the community's expectation for what phenolics can further offer is on the rise. As our knowledge on phenolic chemistries deepens, [18][19][20] the paradigm that drives current research is shifting from simply "where to apply" to a more critical one, regarding "how to apply well." Controlled manipulation of phenolic chemistries and related materials, in a spatiotemporally defined manner, has recently received priority.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such adhesives promise complex functions, which reach from enzymatically activated adhesion, to structurally defined adhesive sites, material specific adhesives, self-healing properties or activatable cohesion control mechanisms. [18][19][20][21][22][23][24][25][26][27] Zhong and co-workers demonstrated on a protein level the possibilities by fusing the mfp3&5 that constitute the adhesive interface in the mussel glue apparatus with Amyloid Ab, recognized for b-sheet formation. 28 Mimicking functional aspects of these complex fusion proteins with artificial mussel glue proteins of reduced complexity would bridge the gap between cost-intensive proteins and synthetic Dopa-bearing polymers.…”
mentioning
confidence: 99%